Understanding key factors for strengthening Nepal’s healthcare needs: health systems perspectives - Neha Dumka; Aayushi Gurung; Erin Hannah; Sonu Goel; Atul Kotwal (Journal of Global Health Reports)
# Background Nepal’s health policy environment and health-care delivery system has changed over the last 25 years, during which it witnessed a significant progress in improving citizens’ access to healthcare services. However, a combination of factors intrinsic to the nation continue to influence health service delivery producing variable health outcomes. Given the nation’s target towards achieving universal health coverage and sustainable development targets, there is a need to review and understand the functioning of Nepal’s health system, its strengths, challenges, and opportunities. The review aims to explore the key health system factors influencing health services and healthcare needs, and forge actionable recommendations for the future. # Methods The review followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for identifying the relevant literature between 2001 and 2023. A total of 300 articles were obtained from the initial search, out of which 42 full text articles were selected for an in-depth review. The literature was analysed to identify the broad themes relevant to Nepal’s health system, and the findings were synthesized narratively under each theme. # Results The review highlights various factors influencing health services and healthcare needs by describing the historical development of Nepal’s healthcare delivery system, its current scenario, health expenditure, health system challenges and opportunities ahead. The evolution of Nepal’s health system has been both significant and responsive. # Conclusions The change in the governance structure and adoption of primary healthcare approach present the nation with ample opportunities to further the scope of the nation’s existing health sector initiatives and outcomes.